CYBERLOAFING DAN KINERJA KARYAWAN : EFEK MODERASI SELF CONTROL: (STUDI PADA USAHA KECIL DAN MENENGAH KOTA KUPANG) - Maria C.B Manteiro; Amram Rohi Bire (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the effect of cyberloafing on the performance of MSME employees in Kupang City and how self-control moderates the relationship between cyberloafing and MSME employee performance in Kupang City. Method: The study uses a quantitative method with multiple linear regression analysis techniques and Moderated Regression Analysis (MRA) with the assistance of SPSS. The research sample consisted of 48 respondents from 12 MSMEs spread across 4 regional clusters in Kupang City, with the criteria of employees in MSMEs with top to middle-level positions, 2) having worked for more than 2 years, and 3) who usually work and can access the internet.Results: The research results show that cyberloafing has a negative and significant effect on employee performance, meaning that the more frequently employees engage in cyberloafing during working hours, the lower the performance produced. Meanwhile, self-control positively and significantly moderates the relationship between cyberloafing and employee performance, meaning that the higher the self-control ability of employees, the smaller the negative impact of cyberloafing on their performance. Conclusion:These findings are in line with the Conservation of Resources (COR) Theory, which explains that individuals try to preserve resources such as energy, time, and attention so that they are not wasted. Self-control acts as a psychological resource that enables employees to refrain from harmful behaviors and maintain performance even when facing the temptation of cyberloafing. Keywords: Cyberloafing, Employee Performance, Self-Control